Craving mediates the association between momentary pain and illicit opioid use during treatment for opioid‐use disorder: an ecological momentary assessment study. (29th December 2020) - Mun, Chung Jung; Finan, Patrick H.; Epstein, David H.; Kowalczyk, William J.; Agage, Daniel; Letzen, Janelle E.; Phillips, Karran A.; Preston, Kenzie L.
Abstract: Aim: To assess the role of momentary pain on opioid craving and illicit opioid use among individuals receiving opioid agonist treatment. Design: Observational study using ecological momentary assessment. Setting: The National Institute of Drug Abuse Intramural Research Program in the United States. Participants: Fifty‐six adults who qualified for opioid agonist treatment. Measurements: Participants completed randomly prompted assessments of pain severity, stress, negative mood, opioid craving and illicit opioid use for a mean of 66 days [standard deviation (SD) = 27]. Urine samples were collected two to three times/week throughout. Findings: Almost 70% of participants reported moderate average pain severity in the past 24 hours at intake and 35% of participants reported chronic pain. There were no significant differences in percent of opioid‐positive urine samples ( P  = 0.73) and average level of opioid craving during the study period ( P  = 0.91) among opioid agonist treatment only patients versus opioid agonist treatment patients with chronic pain. However, momentary pain severity significantly predicted concurrent opioid craving [ B  = 0.02, 95% confidence interval (CI) = 0.01, 0.04], over and above stress and negative mood. Momentary opioid craving, in turn, significantly predicted illicit opioid use that was assessed in the next moment [odds ratio (OR) = 1.72, 95% CI = 1.12, 2.64), while controlling for autocorrelation and the effects of pain, negative mood and stress. Momentary opioid craving significantly mediated the prospective association between momentary pain and illicit opioid use (95% CI = 0.003, 0.032). Exploratory analysis revealed that momentary pain severity also significantly moderated the momentary association between stress and opioid craving ( B  = 0.02, 95% CI = 0.00, 0.04), such that when momentary pain severity increased, the association between the two intensified. Conclusions: Among people receiving opioid agonist treatment, momentary pain appears to be indirectly associated with illicit opioid use via momentary opioid craving.